The Teachers’ Personality Traits Influence on Self-determination - Juodkūnė, Inga (Pedagogika, 2015)
This study focuses on the relationship between teachers’ personality traits and selfdetermination. The basic personality traits are defied by the Big Five model. Big Five is understood as personality dispositional traits. Self- determination theory (SDT) is a macrotheory of motivation (Deci & Ryan, 2008), which describes not only the internal and external motivation, but also a motivation. In this article Self-Determination is the meaning of the global motivation from the hierarchical model of motivation developed by Vallerand R. (1997). The global motivation is described as a general tendency to base one’s actions on intrinsic/extrinsic motives (Vallerand, 2000). The purpose of this study is to analyze the relationship between teachers’ personality traits and global motivational orientation (in SDT context), which consists of internal, external motivation and a motivation. The hypothesis is that teachers’ personality traits predict self-determination. Participants: the sample consisted of 241 Lithuanian teachers: 32 of them (13.3 %) men, 206 (85.5 %) women, 3 (1.2 %) respondents’ gender were undisclosed. The age of respondents varied from 23 up to 75 age (M = 44.5; SD = 10.5). In the study were used two measuring instruments: personality traits questionnaire (NEO – FFI, Costa, McCrae, 2012) and the global motivation scale (GMS – 28; Guay et al., 2003). In the research was used Lithuanian version of Global motivation scale and it’s psycho-metric characteristics (Urbanavičiūtė, Kairys, Juodkūnė, Liniauskaitė; 2013). The relationship between teachers‘personality traits and motivational orientations, self-determination were analyzed using multiple linear regression model. The results show that the hypothesis - teachers’ personality traits predict self-determination, confirmed in part. Personality traits explains 21 % of the test variance. Thee personality traits (openness, extraversion, neuroticism) have the greatest influence to predict overall index of self-determination (SDI). The extraversion and openness have a positive influence on SDI and neuroticism – negative. Agreeableness and consciousness don‘t influence on the index of selfdetermination. The results show that personality traits can predict more accurately the intrinsic motivation rather than external motivation and a motivation. Extraversion, as personal trait, from all file basic personal traits has a biggest influence on self- determination. Extraversion has influence on orientations of inner motivation (To know, To experience and To achieve) and external motivation (regulation and identification). For orientations of external motivation- Introjection and a motivation - extraversion don’t have a direct influence. Openness to experience have a direct influence on inner motivational orientation To know and To experience. For external motivation openness to experience don’t have an influence, but this personal trait can predict a motivation (identified negative direct influence). Agreeableness personal trait predicts one of inner motivation types- To achieve (positive direction of influence), external- Regulation (negative direction of influence) and lack of motivation (positive direction of influence). Personal trait of awareness has influence on prediction of inner motivation, but not on external motivation. Awareness has direct influence on orientations of inner motivation To know and To achieve. Neuroticism has direct influence on general self- determination level, but not on the different orientations of internal and external motivation. Influence of personal traits for teachers self-determination, additional independent variables: respondents age and working experience, help to explain more accurately (higher R2 coefficient). Age and working experience of pedagogical work don’t have influence on prediction of inner motivation, but it makes influence on external motivation (regulation and introjection.) Limitation. Observing all the results of the research, it’s important to mention that main limitation of this research is short version of Big Five questionnaire. Because of that reason, explaining results were questions about what specific characteristics, who belong to one or another trait, have a direct influence to the results. Another important moment is in regression models, without personal traits independent variables were chosen age and working experience of teachers. But, to make a final conclusion about age influence to motivation, would be more objective to lean on results of longitudinal research.